Zahn's `infarcts' of the liver. Issue 5 (September 1966) - Horrocks, P.; Tapp, E.
Abstract : Three patients were found at necropsy to have Zahn's `infarcts' of the liver. In one of these cases the `infarct' merely showed severe centrilobular congestion. In the other two cases there was centrilobular necrosis, and in one of these early fibrosis was seen. Portal vein occlusion was present in all three cases and this had followed splenectomy in two of them. There was no evidence of hepatic artery or vein occlusion. Circulatory failure is considered to have played a part in the pathogenesis of the lesions.